Exploring associations between sprinting mechanical capabilities, anaerobic capacity, and repeated-sprint ability of adolescent ice hockey players - Glaude-Roy, J.; Pharand, P.; Brunelle, J.-F.; Lemoyne, J. (Frontiers in Physiology, 2023)
Introduction Sprinting ability and anaerobic capacities are the determinant variables of the performance of ice hockey players. Recent research in sprinting showed the existence of distinct force-velocity (F-V) profiles, but the link between these profiles and anaerobic capacities remains unclear. This study explores the associations between F-V variables and anaerobic capacities among cohorts of highly trained adolescent ice hockey players.